Ayat-Ayat Hukum dalam Alquran Mengatur Hubungan Sesama Manusia - Hendrianto, Hendrianto; Elfalahy, Lutfi (Institut Agama Islam Negeri Curup, 2021)
This study aims to reveal the legal verses in the Koran, especially the legal verses about human relationships (habluminannas) that have been written in the Koran, as a guide or reference for Muslims. Especially in the case, the number of verses regarding muamalah law is relatively small, especially when compared to the law verses on worship. While the development of life seems to continue to change. while the verse has no changes and additions. This research was conducted with literature study, data collection techniques using documentation techniques with data analysis, namely content analysis. The results show that the verses of muamalah law are classified into 7 (seven) sections, including those related to family law, civil law, criminal law, procedural law, administrative law, economic law, and finance. The verse of law regulates fellow human beings or muamalahs which provide little opportunity for Muslims to implement muamalah activities in accordance with the guidelines contained in the Koran and Hadith, if not explicitly explained it is supported by other legal products such as ushul fiqh and kaedah- fiqh principles.